Chapter 4 Numerical Modelling of Industrial Induction - Vazquez, R. (InTechOpen, 2011)
Induction heating is a physical process extensively used in the metallurgical industry for different applications involving metal melting. The main components of an induction heating system are an induction coil connected to a power-supply providing an alternating electric current and a conductive workpiece to be heated, placed inside the coil. The alternating current traversing the coil generates eddy currents in the workpiece and by means of ohmic losses the workpiece is heated